Base-specific mutational intolerance near splice sites clarifies the role of nonessential splice nucleotides - Zhang, Sidi; Samocha, Kaitlin E.; Rivas, Manuel A.; Karczewski, Konrad J.; Daly, Emma; Schmandt, Ben; Neale, Benjamin M.; MacArthur, Daniel G.; Daly, Mark J. (Genome Research, 2018)
Variation in RNA splicing (i.e., alternative splicing) plays an important role in many diseases. Variants near 5′ and 3′ splice sites often affect splicing, but the effects of these variants on splicing and disease have not been fully characterized beyond the two “essential” splice nucleotides flanking each exon. Here we provide quantitative measurements of tolerance to mutational disruptions by position and reference allele–alternative allele combinations. We show that certain reference alleles are particularly sensitive to mutations, regardless of the alternative alleles into which they are mutated. Using public RNA-seq data, we demonstrate that individuals carrying such variants have significantly lower levels of the correctly spliced transcript, compared to individuals without them, and confirm that these specific substitutions are highly enriched for known Mendelian mutations. Our results propose a more refined definition of the “splice region” and offer a new way to prioritize and provide functional interpretation of variants identified in diagnostic sequencing and association studies.
10.1101/gr.231902.117